ANALISIS KETERAMPILAN SOSIAL MENGGUNAKAN FIRO-B PADA AUDITOR INTERNAL PEMERINTAH DI PROVINSI BENGKULU - Lismawati Lismawati; Emilyan Inzar; Jaka Isgiyarta; Novita Sari (UNIB Press, 2020)
This study aims to analyze and prove whether there are differences in the level of social skills of internal auditors in terms of culture, gender and age. This study uses an internal auditor working in the Bengkulu Provincial Audit Board (BPKP) as a sample. Data were analyzed using the Fundamental Interation Relationship-Behavior (FIRO-B) score and independent sample t-test with the SPSS program. The results showed that there were no significant differences in the level of social skills between the internal auditors of different cultures, genders and ages of the internal auditors working in the Bengkulu Province Audit Board (BPKP). The results of this study provide research evidence that there is no difference in the ability of social skills in terms of cultural, gender and age differences.